Option( c ) is the correct one.
-2x +y= -3
x= (3+y)/2
By executing the value in second equation
{-(3+y)/2} +2y =3
( -3-y +4y)/2 =3
-3 +3y =6
3y = 9
y = 3
Again by substituting the value of y in any of the equation
-2x +y =-3
-2x =-6
x= 3.
Solve for c by simplifying both sides of the equation, then isolating the variable.
Exact form: c = -4/9, 2
Decimal form: c = -.4, 2
<h3>
Answer: -5 < x < 2</h3>
Explanation:
The expression -2x means -2 times x. To undo this, we divide all parts of the inequality by -2. Dividing by a negative number will flip the inequality sign. We go from "less than" to "greater than"
-4 < -2x < 10
-4/(-2) > x > 10/(-2) .... inequality signs flip
2 > x > -5
-5 < x < 2
This unknown number x is between -5 and 2. It cannot equal -5. It cannot equal 2.
The inverse of the function is h(x)=4x+48
Eight hundredths
0.08
You already got it with the number part ;)